2017
DOI: 10.1093/nar/gkx1009
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant ribonucleotide incorporation and multiple deletions in mitochondrial DNA of the murine MPV17 disease model

Abstract: All DNA polymerases misincorporate ribonucleotides despite their preference for deoxyribonucleotides, and analysis of cultured cells indicates that mammalian mitochondrial DNA (mtDNA) tolerates such replication errors. However, it is not clear to what extent misincorporation occurs in tissues, or whether this plays a role in human disease. Here, we show that mtDNA of solid tissues contains many more embedded ribonucleotides than that of cultured cells, consistent with the high ratio of ribonucleotide to deoxyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 35 publications
(53 reference statements)
3
53
0
Order By: Relevance
“…Instead, subjects with a complex phenotype, usually combining ataxia and PEO, had some of the highest levels of mtDNA among the SPG7 patients (250 per haploid nuclear DNA compared to 153 in pure spastic forms). Multiple deletions or depletion are alternative outcomes in a number of single‐gene mtDNA disorders, and in a mouse model of mtDNA disorder, multiple deletions and depletion have been reported in different tissues . The latter study led to the suggestion that mtDNA depletion is a consequence of slow DNA replication to prevent stalling and the formation of deletions and thus avoid the development of PEO.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, subjects with a complex phenotype, usually combining ataxia and PEO, had some of the highest levels of mtDNA among the SPG7 patients (250 per haploid nuclear DNA compared to 153 in pure spastic forms). Multiple deletions or depletion are alternative outcomes in a number of single‐gene mtDNA disorders, and in a mouse model of mtDNA disorder, multiple deletions and depletion have been reported in different tissues . The latter study led to the suggestion that mtDNA depletion is a consequence of slow DNA replication to prevent stalling and the formation of deletions and thus avoid the development of PEO.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated number of rNMPs per double-stranded mtDNA molecule ranges from 36 and 54 rNMPs in cultured HeLa and primary fibroblast cell lines, respectively [9], to 65 rNMPs in mouse liver [8]. In accordance with these numbers, Moss et al [65] reported a higher frequency of rNMPs in solid tissues than in cultured cell lines. The location of mtDNA rNMPs has been mapped using next-generation sequencing approaches, and they appear to be randomly distributed across the mammalian mitochondrial genome [9,65].…”
Section: Features Of Mtdna and Its Replicationmentioning
confidence: 85%
“…In accordance with these numbers, Moss et al . reported a higher frequency of rNMPs in solid tissues than in cultured cell lines. The location of mtDNA rNMPs has been mapped using next‐generation sequencing approaches, and they appear to be randomly distributed across the mammalian mitochondrial genome .…”
Section: Ribonucleotides Are Incorporated During Mtdna Replication Anmentioning
confidence: 92%
See 2 more Smart Citations